VOLUNTEERISM ACTIVITIES TOWARDS PLACE MAKING: CASE STUDY PITT STREET, PENANG - Abd Rahim, Muhd Nadzmi; Mohamad, Diana (PLANNING MALAYSIA, 2020)
Through the World Giving Index 2014 Survey by the Charities Aid Foundation (CAF), Malaysia is ranked 76th out of 160 countries in terms of willingness to spend time to engage in volunteerism, provide financial assistance to others and be prepared to help non-Malaysian citizens (Lili Wang & Robert Ashcraft, 2014). Place making is a concept used in the planning, design and management of public-spaces in urban areas development; where it influences social development of a location. Volunteering activities should be determined by the type, place and time of a place where the activity is conducted. This study focuses on the UNESCO World Heritage Site in Penang (Malaysia) namely Street Pitt. Questionnaire survey was conducted in order to understand the sociability and volunteerism activity of the study area. The variables include types and frequency of volunteerism, level of involvement and factors influencing place making. The finding shows that Street Pitt manages to be one of the places that apply all elements contained in the concept of making place. In the social aspect, this area has become a popular volunteerism activity and also one of the most visited tourist spots.